Hydrogel local drug delivery systems for postsurgical management of tumors: Status Quo and perspectives - Ziqiao Zhong; Lu Gan; Ziyi Feng; Wenhao Wang; Xin Pan; Chuanbin Wu; Ying Huang (Materials Today Bio)
Surgery is one of the primary treatments for solid tumors. However, the incomplete resection of tumor cells and the immunosuppressive microenvironment make the issue of postsurgical tumor recurrence a great challenge. Furthermore, a wide range of requirements, including ensuring effective hemostasis, implementing prophylactic measures against infection, and promoting wound healing, were also raised in the postsurgical management of tumors. To fulfill these demands, multiple hydrogel local drug delivery systems (HLDDS) were developed recently. These HLDDS are expected to offer numerous advantages in the postsurgical management of tumors, such as achieving high local drug concentrations at the lesion, efficient delivery to surgical microcavities, mitigating systemic side effects, and addressing the diverse demand. Thus, in this review, a detailed discussion of the diverse demands of postsurgical management of tumors is provided. And the current publication trend on HLDDS in the postsurgical management of tumors is analyzed and discussed. Then, the applications of different types of HLDDS, in-situ HLDDS and non-in-situ HLDDS, in postsurgical management of tumors were introduced and summarized. Besides, the current problems and future perspectives are discussed. The review is expected to provide an overview of HLDDS in postsurgical management of tumors and promote their clinical application.